Parcelamento de nitrogênio na cultura do trigo e seus efeitos nos componentes de rendimento e qualidade fisiológica de sementes produzidas em terras baixas - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Nitrogen is one of the fertilizers required in greater quantity by the wheat crop, several works show their responses in relation to the different times of application of nitrogen in coverage, in this way it becomes an important cultural tract for the definition of productivity. The objective was to evaluate if the influence on yield components and physiological quality of seeds in wheat cultivars according to the different times of application of nitrogen in coverage. The experiment was carried out in the experimental area of the UNIPAMPA campus Itaqui located on the western border of the state of RS, consisting of the cultivars Tbio Sonic, OR 1401 and Tbio Sinuelo, seeded in the density of 350 viable seeds / m² in a completely randomized design (DIC) (50% in V3 and 50% in floral differentiation (DIF)), T3 (30% in V3, 50% in DIF and 20% in flowering (FL)), T4 (100% in DIF), T5 (50% in V3, 30% in DIF and 20% FL) and T6 (80% in DIF and 20% in FL), totaling 72 plots. The variables evaluated were plant height at flowering (EST), number of fertile stalks (COF), green shoots (VOC), total stalks (TOC), leaf dry matter (MSF), stalk dry matter (DM), number of grains per spike (GE), number of grains / m² (GM), weight of a thousand grains (PM), hectoliter weight (PH), productivity (PD) , germination (G), root length (CR), aerial part (CPA) and total number of seedlings (CT). Treatment (T1) elevated EST, MSF, MSC, MSE MST and GM. T4 and T6 treatments increased the number of green shoots and reduced EST, MSF, MSC, MSE, MST, GE and GM. The treatments T1 and T5 generated higher productivity and T4 and T6 limited it. For Tbio Sonic T1 treatment generated higher physiological seed quality, T5 reduced it. However for OR 1401 no difference was found. In relation to Tbio Sinuelo, the use of the T6 treatment caused a higher physiological quality and the treatments T1 and T2 restricted it.
Keywords: Triticum aestivum; Adubação; Tratos culturais; Fenologia; Fertilizing; Cultural tract; Phenology; CNPQ::CIENCIAS AGRARIAS